PENINGKATAN KETERAMPILAN GERAK DASAR TENDANGAN LURUS PENCAK SILAT MENGGUNAKAN MEDIA PALANG MELALUI PENDEKATAN METODE DEMONSTRASI - Chairullah Ridha; Syamsul Arifin (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2013)
Improved Basic Skills Kicking Motion Pencak Silat Straight Through Approach Using Cross Media Methods Demonstration. The main problem in this study is the lack of understanding of  learners when teachers convey only with theory, less mastered the teaching of skills and expertise knowledge of martial arts, the students have not been able to perform a straight kick well and unavailability of improving the skills of learning martial arts. The purpose of this study was to determine whether there is an increase in the basic movement skills using a martial arts kick straight through the cross media approach to the method of demonstration classes students Bakti VB Handil Batola Elementary School. The method used in this study methods of classroom action research (CAR) is in the form of a reflective research. The  observation period  lasted  learning and  data  analysis is  based  on observations made by the supervisor. The subjects were students in the class VB Elementary School Handil Consecrated Batola academic year 2013/2014. The number of students who study the subject of at least 39 people, consisting of 21 students and 18 women's sons. By using a cross media approach through demonstration method can improve basic motor skills of martial arts kick straight at VB class learners SDN Handil Bakti Batola.Keywords: Media crossbar, method demonstrations, basic movement skills of martial arts kick straight.